The Gospel of Coffee Mission, Education and Employment in 19th Century Travancore - Dick Kooiman (ECONOMIC AND POLITICAL WEEKLY, 1984)
Many historians have argued that it was largely the challenge posed by christian missionaries in the nineteenth century that provoked the contemporary social reform movement, the leadership of which gradually moved into the hands of nationalist intellectuals and social workers from all parts of India. Following that line of reasoning, the missionaries ' main contribution may have been to start a movement to purge Hindu society of its most glaring social evils as well as to stimulate a revival and resurgence of Hindu belief and practices, about the last thing the missionaries could have wanted. It is these unintended but nevertheless far-reaching effects of missionary activity that form the main theme of this study of the London Missionary Society (LMS) in nineteenth century Travancore.